Supply chain perspectives for achieving economic growth and environmental sustainability - Kovačič Lukman, Rebeka (Logistics, supply chain, sustainability and global challenges, 2024)
A resilient supply chain is crucial for economic growth and the well-being of economies. However, it contributes to environmental challenges, such as resource extraction, material usage, climate change and biodiversity. This Special Volume of the Journal of Logistics, Supply Chain, Sustainability, and Global Challenges explores current research directions and challenges while offering solutions for sustainable supply chains. The volume examines existing European policy directives and strategies to comprehensively understand sustainable supply chain requirements. It conducts a content analysis of the current research in the field. The authors present valuable theoretical insights and empirical case studies addressing the interplay between sustainable supply chains, economic growth, and environmental impact mitigation. The papers in this Special Volume highlight the holistic and interconnected nature of the supply chain field and emphasise that there is still significant potential for improving supply chain processes to enhance their sustainability.
Keywords: economic growth; environmental impact; gospodarska rast; industrija 4.0; industry 4.0; sustainable supply chains; trajnostne dobavne verige; vpliv na okolje